Practicing harm reduction psychotherapy : an alternative approach to addictions - Denning, Patt , 1950-; Little, Jeannie , 1962- (The Guilford Press, 2012)
"Subject areas/key words: abstinence, addictions, addictive behaviors, alcoholism, counseling, dependence, drug abuse, dual diagnosis, harm reduction, interventions, psychotherapy, recovery, substance use disorders, treatments Brief Summary: This acclaimed clinical guide has helped thousands of clinicians put the proven principles of harm reduction into practice with therapy clients who have substance use problems. Written by pioneers in the field, the book shows how to do effective therapeutic work with people still using alcohol or other drugs. It provides clear guidelines for conducting comprehensive assessments, making collaborative treatment decisions, and implementing interventions that combine motivational, cognitive-behavioral, and psychodynamic strategies. The focus is reducing drug-related harm while also addressing co-occurring psychological and emotional difficulties. Detailed clinical illustrations are featured throughout"-- Provided by publisher